2015
DOI: 10.1002/adhm.201500102
|View full text |Cite
|
Sign up to set email alerts
|

Engineered Microtissues Formed by Schiff Base Crosslinking Restore the Chondrogenic Potential of Aged Mesenchymal Stem Cells

Abstract: A universal method for reproducibly directing stem cell differentiation remains a major challenge for clinical applications involving cell-based therapies. The standard approach for chondrogenic induction by micromass pellet culture is highly susceptible to interdonor variability. A novel method for the fabrication of condensation-like engineered microtissues (EMTs) that utilizes hydrophilic polysaccharides to induce cell aggregation is reported here. Chondrogenesis of mesenchymal stem cells (MSCs) in EMTs is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
29
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 55 publications
3
29
0
Order By: Relevance
“…However, the different ability of these composite gels to promote chondrogenic differentiation of encapsulated BMSCs found in this study, might be due to the different quantity of PRP, which is correlated with the amount of growth factors loaded, as has been also shown by others (Millan, Cavalli, Groth, Maniura‐Weber, & Zenobi‐Wong, ). Millan et al () found that addition of TGF‐β3 in engineered microtissues (EMTs) greatly influenced the chondrogenic differentiation of the encapsulated MSCs. The EMTs loaded with either 50 or 75 ng of TGF‐β3 expressed higher amounts of sulfated glycosaminoglycan and more Type II collagen than the samples loaded with 25 ng of TGF‐β3, only.…”
Section: Discussionsupporting
confidence: 50%
“…However, the different ability of these composite gels to promote chondrogenic differentiation of encapsulated BMSCs found in this study, might be due to the different quantity of PRP, which is correlated with the amount of growth factors loaded, as has been also shown by others (Millan, Cavalli, Groth, Maniura‐Weber, & Zenobi‐Wong, ). Millan et al () found that addition of TGF‐β3 in engineered microtissues (EMTs) greatly influenced the chondrogenic differentiation of the encapsulated MSCs. The EMTs loaded with either 50 or 75 ng of TGF‐β3 expressed higher amounts of sulfated glycosaminoglycan and more Type II collagen than the samples loaded with 25 ng of TGF‐β3, only.…”
Section: Discussionsupporting
confidence: 50%
“…of studiesReferencesCell SourceNo. of studies a ReferencesHuman73[48, 50, 52, 53, 168236]Bone marrow62[48, 5053, 164, 168, 170173, 177180, 182185, 187, 188, 192, 195–197, 203, 206–210, 212, 216, 217, 219, 221, 223, 227, 230, 232235, 237–255]Rabbit17[240242, 246, 249, 252, 255–265]Adipose36[66, 169, 175, 176, 181, 186, 189, 193, 194, 199, 201, 202, 211, 214, 216, 218220, 224, 228, 229, 231, 235, 242, 256, 257, 260269]Bovine5[51, 164, 243, 245, 270]Synovium9[174, 191, 200…”
Section: Resultsmentioning
confidence: 99%
“…of studies (%)ReferencesGrowth factorNo. of studies (%)ReferencesTGF-β148 (44%)[50, 169175, 189, 190, 192, 193, 195, 199, 202, 208, 210, 211, 213, 214, 216, 217, 220, 222224, 228, 230–232, 234, 235, 244, 246, 249, 252256, 258, 260263, 266, 267, 270]SOX-51 (1%)[204]TGF-β332 (29%)[51, 162, 164, 168, 177, 181184, 197, 200, 205207, 218, 223225, 227, 237, 239, 240, 245, 247, 248, 250, 251, 257, 259, 267, 268, 270]SOX-61 (1%)[204]BMP-213 (12%)[188, 202, 213, 219, 225227, 229, 264, 265, 267, 270, 271]WNT3A1 (1%)…”
Section: Resultsmentioning
confidence: 99%
“…As an important class of compounds, Schiff bases have received much attention in the wide variety of fields due to structural varieties and unique characteristics such as preparative accessibility, varied coordination ability, thermal stability, biological activities and catalysis properties [8][9][10]. Schiff base ligands are able to coordinate with many different metals and stabilize them in various oxidation states [11][12][13].…”
Section: Introductionmentioning
confidence: 99%